EVOLUTION OF THE PHOTOMETRIC PROPERTIES OF THE MAGNETIC CATACLYSMIC BINARY QQ VUL IN 1986-88 - A. V. Halevin; I. L. Andronov; S. V. Kolesnikov; G. N. Kirneridze (Odessa Astronomical Publications, 2017)
The long term activity variations of polar QQ Vul in 1986-88 are reported.